STRATEGI PENGELOLAAN KELAS UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Sofyan Iskandar; Primanita Sholihah Rosmana; Mufidatul Husna; Pani Herlina; Vika Andria Sukmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Because critical thinking skills are an important factor for students, critical thinking skills training is needed. One way to improve students' critical thinking skills is through effective classroom management methods. This article aims to explore how classroom management methods can improve students' critical thinking abilities in secondary schools. This research uses a qualitative approach with a descriptive approach. The qualitative descriptive approach utilizes qualitative data presented descriptively to obtain accurate data and emphasize the results. The research results show that a classroom management approach in secondary schools can help improve students' critical thinking skills.